2005
DOI: 10.5194/angeo-23-1295-2005
|View full text |Cite
|
Sign up to set email alerts
|

High-latitude electromagnetic and particle energy flux during an event with sustained strongly northward IMF

Abstract: Abstract. We present a case study of a prolonged interval of strongly northward orientation of the interplanetary magnetic field on 16 July 2000, 16:00-19:00 UT to characterize the energy exchange between the magnetosphere and ionosphere for conditions associated with minimum solar windmagnetosphere coupling. With reconnection occurring tailward of the cusp under northward IMF conditions, the reconnection dynamo should be separated from the viscous dynamo, presumably driven by the Kelvin-Helmholtz (KH) instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 56 publications
8
58
1
Order By: Relevance
“…(6) is 53.49 kV, in good agreement with Korth et al (2005). It is interesting to note that Korth et al (2005) found that the potential drop associated with viscous interaction is less than ∼5 kV, or about 9 times smaller than the potential drop caused by high-latitude reconnection. Figure 9 (right panel) shows the ionospheric electrostatic potential patterns in the southern polar cap calculated for case 1.…”
Section: Model Calculation Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…(6) is 53.49 kV, in good agreement with Korth et al (2005). It is interesting to note that Korth et al (2005) found that the potential drop associated with viscous interaction is less than ∼5 kV, or about 9 times smaller than the potential drop caused by high-latitude reconnection. Figure 9 (right panel) shows the ionospheric electrostatic potential patterns in the southern polar cap calculated for case 1.…”
Section: Model Calculation Resultssupporting
confidence: 77%
“…(7) gives 32 kV, a good agreement with the Siscoe et al (2001) MHD simulations results. We can check our result by comparing with the polar cap potential drop which was determined by Korth et al (2005). These authors presented a case study of a prolonged interval of strongly northward IMF on 16 July 2000.…”
Section: Model Calculation Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Although this approach breaks down more than a few hours from dawn and dusk and under other circumstances (e.g., northward IMF) when fringing effects dominate the signatures, the magnetic signatures unambiguously indicate the presence of the currents even if one cannot confidently 'infer the current density distribution from the data (cf. Fung and Hoffman, 1992;Waters et al, 2001;Korth et al, 2005). In addition, particle data provide useful correlative observations of the current carriers, and the FIPS and EPS sensors which measure composition, velocity and density for both ions and electrons wjll, in principle, give a direct measurement of current.…”
Section: How Will Messenger Detect and Map Field-aligned Currents Andmentioning
confidence: 99%